Aplikasi Jenis Pupuk Organik pada Tanaman Padi Sistem Pertanian Organik - SUPARTHA, I NYOMAN YOGI; WIJANA, GEDE; ADNYANA, GEDE MENAKA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol. 1, No. 2, Oktober 2012, 2012)
ABSTRACT Application Types of Organic Fertilizer for Rice ( Oryza sativa L . ) in Organic Farming Systems Rice plants ( Oryza sativa L. ) is a plant food as an energy source that is generally consumed by the people of Indonesia . Nearly half the world's population , especially in Asia dependent of the rice plant . Once the importance of rice that could lead to crop failures widespread social unrest . One of the efforts to increase the productivity of rice plants is to replenish nutrient needs through fertilization . This experiment aims to find the best combination between solid organic fertilizer with liquid organic fertilizer on the growth and yield of rice plants . The results showed that the combination treatment of solid organic fertilizer and liquid organic fertilizer does not significantly affect plant growth variables , but the real influence the outcome of the rice plant . The addition of liquid organic fertilizer in rice planting organic system able to increase the yield of dry grain yields of 4.4 % - 17.4 %. Results of dry grain harvests and grain yield obtained at the highest oven dry fertilizer additions AA -01 (5.07 tonnes / ha dry grain harvest , and 3.94 tonnes / ha oven dried grain ). Suggestions can be thought of , in organic rice farming system suggested combining solid fertilizer with liquid fertilizer , so that the growth and yield can be improved , and the need to study solid organic fertilizers and other liquid organic fertilizer in order to obtain higher yields Keyword: organic fertilizer, growth and yields, organic farming system s
Keywords: organic fertilizer,growth and yields, organic farming systems